Usm New Hostel (Desasiswa Tekun) Slope Stability Studies - Awang Redzuan, Awang Zaideladha (Universiti Sains Malaysia, 2005)
The aim of this study is to utilize the GIS techniques for slope instability assessment and prediction in the University Sains Malaysia main campus new hostel area, in the Penang State, peninsular Malaysia. GIS, can assist in terms of speeding up processing and moreover in the hazard zonation and prediction assessment. Nowadays, the problems of slope failure have become more serious. High speed development without hesitation and doubt to build a structure on hill due to the shortage of lands for certain countries contributed to the increasing of slope failure case. By this reason, the work of maintenance for reduce the slope failure become more important nowadays, so the system are needed for some person such as consultant, contractor, developer and government to prevent the slope from fail effectively. The research of project has a purpose to produce a system which can help to reduce the risk to slope failure by using ERDAS Imagine Version 8.3. Few steps already be recognize in this research such as data collection, confirm type of data which used to analysis the slope stability and system monitoring. The results are produced in images and these images should show the factor of safety for the entire area of a hill. From these maps, we can know and define the danger zones on a hill. The result of analysis would be check by using Slope/W for determined the effectiveness of system. These software are user friendly and they can be used to do so many spatial analysis and others. Hopefully in this project, the methodology of analyzing slope stability using these two programs can be beneficial to those who are interested in doing slope stability analysis.